Gambaran Kejadian Kekurangan Energi Kronis (KEK) pada Mahasiswa Fakultas Kesehatan Masyarakat Universitas Halu Oleo - Irma Yunawati; Windy Racmayati Apandi; Anika Nur Halisa; Cinta Stevi Syela; Asra Zaima; Nilam Husnul Khatima; Nurzahrah Ahmad (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Upper Arm Circumference (LILA) is one of the indicators used in Indonesia to assess the risk of Chronic Energy Deficiency (KEK) in pregnant women and adult women. Chronic lack of energy for a long time causes the immune system to decrease so that the body is susceptible to infectious diseases, the decreased ability to concentrate which occurs is related to a decrease in iron stores. Upper Arm Circumference (LILA) measurement aims to analyze the relationship between Upper Arm Circumference (LILA) and the incidence of Chronic Energy Deficiency (KEK) in students at the Faculty of Public Health, Halu Oleo University. The method used is data analysis, involving measuring LILA and collecting data regarding nutritional status and factors that have the potential to influence KEK. The results of the analysis show that there is a significant relationship between LILA size and the incidence of CED. Of the 50 respondents studied, 52% experienced CED with a LILA size of less than 23.5 cm, which indicates the existence of serious nutritional problems among this population. It is hoped that this research will provide useful information for universities and health workers in efforts to prevent and treat nutritional problems among students.